Effect of echium oil combined with phytosterols on biomarkers of atherosclerosis in LDLr‐knockout mice: Echium oil is a potential alternative to marine oils for use in functional foods. Issue 10 (24th April 2015) - Botelho, Patrícia Borges; Guimarães, Jéssica Pereira; Mariano, Karina Rocha; Afonso, Milessa da Silva; Koike, Márcia Kiyomi; Lottenberg, Ana Maria Pita; Castro, Inar Alves
<x xml:space="preserve">Abstract</x> Bioactive compounds may be an alternative approach to prevent atherosclerosis. To evaluate this hypothesis, LDLr‐knockout mice were supplemented with omega‐3 fatty acids from Echium oil (10.24 mg/d of oil with 1, 14 mg/d of SDA and 9.06 mg/d of ALA) equivalent to 0.7 mg/d of EPA after conversion, combined or not with phytosterols (0.76 mg/d), during the first 2 months of life. Subsequently, dyslipidaemia was induced by a high‐fat diet for the following 2 months. Echium oil, isolated or combined with phytosterols, improved lipid profile in plasma reducing triacylglycerol (90.3 ± 7.6 mg/dL) and VLDL‐c (18.0 ± 1.5 mg/dL) concentrations when compared with Control (115.8 ± 9.4 mg/dL and 23.2 ± 1.9 mg/dL, respectively). Echium oil also increased catalase (5.66 ± 0.13 U/mg protein) while Echium oil combined with phytosterol increased glutathione peroxidase activity (26.27 ± 0.10 U/mg protein) when compared with Control (5.18 ± 0.10 U/mg protein and 25.31 ± 0.16 U/mg protein, respectively). In addition, groups receiving Echium oil have reduced malondialdehyde concentration in liver (p = 0.05). However, no difference was observed in fatty streak lesions when compared with Control. Isolated phytosterols did not change cholesterol absorption and increased lesion area compared with control group. This result can be associated with the high dose applied in the first step of supplementation and with the form of supplementation (gavage). Practical applications: One factor that contributes to the number of deaths from cardiovascular disease is that pharmacological interventions usually start too late in life. For this reason, functional foods development is a very important strategy to prevent atherosclerosis, since their inclusion in diet can start much earlier. However, it represents a challenge because many physiological responses from chronic consumption of bioactive compounds are still unknown. In this study, considering the positive results on triglyceridemia and oxidative stress biomarkers, we suggest that Echium oil can be an alternative for development of functional foods. We selected Echium oil due to its higher proportion of stearidonic fatty acids (pro‐EPA) and lower sensory limitation than marine oils. <inline-graphic xlink:href="ark:/27927/pgkfn973hp" content-type="ejlt201500004-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Echium oil improves lipid profile and reduces oxidative stress, while phytosterol increases fatty streak.